2006
DOI: 10.2118/06-03-01
|View full text |Cite
|
Sign up to set email alerts
|

Some History Cases of Long-Term Linear Flow in Tight Gas Wells

Abstract: Many tight gas wells show transient linear flow that lasts for many years. Linear flow is normally associated with hydraulic fractures, but tight gas reservoirs may contain geometrical effects that lead to linear flow behaviour. In this study, long-term linear flow caused by the presence of natural parallel fractures is investigated and a systematic procedure to analyze linear flow in tight gas wells is described. Application of this methodology to production analysis of three tight gas wells, and validation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Long-term linear flow in a large number of wells in tight or shale gas has been observed as early as 1976 (Bagnall and Ryan 1976 causes this phenomenon. Several authors have shown that this linear flow exists in any type of fractures whether they are infinite- (Agarwal et al 1979) or finite-conductivity (Cinco-Ley et al 1978;Samaniego 1981a, 1981b), single or multistage Wattenbarger 2010), hydraulic (Arévalo-Villagrán et al 2001), or natural fractures (Arévalo-Villagrán et al 2006). The difference among these models is the length of this transient linear-flow regime.…”
Section: Methods Developmentmentioning
confidence: 99%
“…Long-term linear flow in a large number of wells in tight or shale gas has been observed as early as 1976 (Bagnall and Ryan 1976 causes this phenomenon. Several authors have shown that this linear flow exists in any type of fractures whether they are infinite- (Agarwal et al 1979) or finite-conductivity (Cinco-Ley et al 1978;Samaniego 1981a, 1981b), single or multistage Wattenbarger 2010), hydraulic (Arévalo-Villagrán et al 2001), or natural fractures (Arévalo-Villagrán et al 2006). The difference among these models is the length of this transient linear-flow regime.…”
Section: Methods Developmentmentioning
confidence: 99%
“…We use a linear flow model to couple fracture-reservoir gas flow because linear flow is the predominant flow regime in shale reservoirs with hydraulic fractures. Transient linear flow usually occurs in unconventional formations and may last for many years (Arevalo-Villagran et al 2006;Tabatabaie and Pooladi-Darvish 2017). The major reason is that linear flow is associated with hydraulic fractures, and the well-fracture geometry results in linear flow behavior (Arevalo-Villagran et al 2006).…”
Section: Fracture and Reservoir Modelsmentioning
confidence: 99%
“…This paper, and others, discusses the behavior of gas wells in long-term linear flow. Several mechanisms are presented that can lead to apparent linear flow behavior, including infinite conductivity fractures extending to the drainage area boundary, anisotropic reservoir system permeability (possibly caused by a directional fracture enhancement trend), or linear deposition channels (Arevalo-Villagran, et al, 2006;Ibrahim and Wattenbarger, 2006). While all of these are possible, for some reason the industry has, in general, taken the first cause (infinite conductivity fractures with no inflow beyond the fracture tips) as the reason for the presumed linear flow signature observed in some production analyses.…”
Section: Application Of the Linear Flow Modelmentioning
confidence: 99%